Simulation of blood flow in arteries with aneurysm: Lattice Boltzmann Approach (LBM). (April 2020) - Afrouzi, Hamid Hassanzadeh; Ahmadian, Majid; Hosseini, Mirollah; Arasteh, Hossein; Toghraie, Davood; Rostami, Sara
Highlights: The blood flow was simulated in the aneurysm using lattice Boltzmann method. Blood was selected as a non-Newtonian fluid. Simulations were carried out for two types of aneurysm. With increasing the Reynolds number, the range of vortexes grows in the aneurysm. Abstract: Background and Objective: In most countries, the higher death rates are due to cardiovascular disease and stroke. These problems often derive from irregular blood flow and the circulatory system disorder. Methods: In this paper, the blood flow is simulated in a created aneurysm in the artery upon using Lattice Boltzmann Method (LBM). Blood is selected as a non-Newtonian fluid which was simulated with power-law model. The lattice Boltzmann results for non-Newtonian fluid flow with power-law model and the curved boundary are compared and validated with previous studies which show a good agreement. In this study, simulations are carried out for two types of aneurysms. For the first aneurysm, three power-law exponents of 0.6, 0.8 and 1.0 at Reynolds number of 100 for three different cases are investigated. Results: The results show that the wall shear stress increases with increasing the power-law exponent. In addition, in the main duct of artery where the velocity is larger, shear stress is lower due to the smaller velocity gradient. For the second Aneurysm, the simulations are done for three Reynolds numbers of 100, 150 and 200, and three Womersley numbers of 4, 12 and 20. The blood flow is pulsating at the inlet such as the real pulsating wave in the blood. Results show that with increasing the Womersley number, the velocity profiles in the middle of the aneurysm are closer at a constant Reynolds number. Conclusions: With increasing the Reynolds number, the range of vortices and values of velocity and tension grow in the aneurysm.